Cognitive foundations of new lexical usage in modern Kazakh, Turkish and Tuvan languages - Bissengali, Akmaral Z.-G.; Burkitbayeva, Shynaray D.; Mankyeeva, Zhamal A.; Kulmanov, Sarsenbay K. (The New Research of Tuva, 2025)
The article explores the cognitive foundations of new lexical usages in contemporary Kazakh, Turkish, and Tuvan languages. The primary focus is on analyzing the influence of globalization, cultural change, and technological advancement on the formation of new lexical units and the transformation of meanings associated with existing concepts. The study addresses three key aspects: the borrowing of foreign words, their adaptation, and the creation of native equivalents to denote new concepts. The linguistic material necessary for the research was collected from the pages of Kazakh, Turkish, and Tuvan periodical press from 2000 to 2025, including newspapers such as Egemen Qazaqstan, Ana tili, Hürriyet, Sabah, and Shyn. The analysis of examples demonstrated that the Kazakh language is significantly influenced by a policy of language modernization aimed at preserving national identity through transliteration and morphological adaptation of borrowed words. In contrast, the Turkish language tends to favor calquing and the creation of original Turkish equivalents, reflecting a long-standing language policy directed toward the “purification” of the language from borrowings. The Tuvan language is more often characterized by hybrid forms of adaptation, where borrowings are integrated with local cultural concepts, thus enabling the preservation of regional cultural specificities in the context of globalization.